In Search for Consumer: New Actors of Social History in the 1920-1930s - Скубій, Ірина (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The article deals with the features of the Soviet consumption’s history in the 1920’s-1930’s. The gender-age approach is utilized to classify consumer groups. In this regard, the objects of scientific analysis are children, men and women who, in spite of their belonging to various social and professional groups, were consumers of goods and services. The methodological potential of the consumption’s history is used to "uncover" new faces of the social history of Soviet society.